Transforming Islamic Boarding Schools Through Neuroscience-Based Change Management: Revitalizing Culture and Arabic Education Models - Mohammad Jailani (Balai Diklat Keagamaan Semarang, 2025)
In the era of rapid technological advancement, the integration of Islamic and scientific cultures in Islamic boarding schools becomes increasingly vital to accommodate the dynamic potential of students. However, many pesantren have yet to implement systematic change management strategies to optimise student development and learning outcomes. This study aims to examine the role of change management in enhancing students’ academic and personal growth at MBS Muhammadiyah Pleret, Yogyakarta. Employing a qualitative case study approach, data was collected through interviews and observations involving religious teachers, students, and staff. The analysis was conducted through data reduction, display, and verification processes. Findings reveal that the combination of theory- and practice-based learning, supported by effective change management, leads to significant improvements in student outcomes. The consistent application of neuroscience principles and the pesantren’s cultural environment positively shapes students’ behavior, motivation, and learning achievements. Biannual data show a steady increase in learning potential over time. The study concludes that the integration of change management in pesantren settings supports better academic results, enriches cultural values, and strengthens school governance. Although a strong correlation between change management and knowledge management was not established, both elements contribute positively to educational enhancement, indicating the need for further exploration.